An MLP-Based ITI Suppression Method for Multi-Head Multi-Track Bit-Patterned Magnetic Recording - Santi Koonkarnkhai; Piya Kovintavewat; Chanon Warisarn (IEEE Transactions on Magnetics, 2025)
Inter-track interference (ITI) is a critical challenge in bit-patterned magnetic recording (BPMR) systems, particularly at high areal densities (ADs) where reduced bit period and track pitch lead to severe interference. This article introduces a novel multi-layer perceptron (MLP)-based ITI suppression method for the three-head three-track (3H3T) BPMR system. Our approach uses an MLP to estimate the main track data and uses iterative decoding to generate soft information, which will then be used to reconstruct and remove ITI for the adjacent tracks. At an AD of 3 Tb/in2 and a bit-error rate (BER) of $10^{-5}$ , simulation results show that the proposed system achieves performance gains of 1 and 6.5 dB compared with the previously proposed 3H3T system and the conventional system with one-head one-track detection, respectively. In addition, our system demonstrates robust performance under challenging conditions, maintaining effectiveness with track mis-registration (TMR) up to 10% and media noise up to 5%. These results indicate that the proposed method can be considered as one of the promising solutions for ultrahigh-density BPMR systems.
Keywords: Magnetic properties of thin films; Iterative Learning Control Systems; Cellular Automata and Applications